Influencing Factors Identification and the Correlation Analysis of Business Environment in the Guangdong-Hong Kong-Macao Greater Bay - Yuli Yu; Haitao Yao; Wanhua Zhuang (Discrete Dynamics in Nature and Society)
The outline of the development plan issued by CPC Central Committee and the State Council for the Guangdong Hong Kong Macao Bay Area clearly pointed out that the Guangdong-Hong Kong-Macao Bay Area should be built into a vibrant world-class urban agglomeration, an international science and technology innovation center, an important support for the construction of the “the Belt and Road,” and a demonstration area for in-depth cooperation between the mainland and Hong Kong and Macao; and a high-quality life circle suitable for living, working, and traveling should be created to become a model of high-quality sustainable development. In order to develop the Guangdong-Hong Kong-Macao Bay Area, it is extremely important to enhance the regional business environment. This paper focuses on five influencing factors: policy support, talent guarantee, market supervision, financial support, and cultural promotion. Based on one-way ANOVA and Cobb Douglas function, this paper makes an empirical study on the two important node cities of Zhuhai and Macao. The results show that (1) different factors have different degrees of significant impact on the regional business environment, among which the industry type has the greatest impact, and the duration of enterprise registration has the least impact; (2) when the factors act alone, there is a significant positive correlation between the evaluation dimensions, but most of the correlation degrees are not much different. Finance and talents are the weaknesses of the business environment in the two cities. (3) When the factors are combined, different factors have significant differences in different regions. Zhuhai mainly benefits from policy support, while Macao mainly benefits from market supervision. (4) Regional integration can produce significant association relationship, among which cultural promotion is an important factor. These five important factors have been effectively identified, which have played a leading role in the further design and development direction of the Guangdong-Hong Kong-Macao Bay Area in the future and have an extremely important enlightenment for the study of the business environment in this region.